Optimization of Pectin Extraction Process from Albedo of Citrus Lemon (Citrus limon) Using Ultrasonic Method - Filianty, Fitry; Alifia, Rachma Nur; Yuliana, Tri; Yusuf, Asep; Putri, Selly Harnesa (Industria: Jurnal Teknologi dan Manajemen Agroindustri, 2024)
Abstract Pectin is an industrial raw material that can form gels, thickeners, and emulsifiers widely applied in the food and non-food industries. Extracting pectin with citric acid solvent using ultrasonic waves is considered more effective and efficient. This study aimed to obtain an optimization model for the pectin production process to produce maximum pectin yield and obtain the optimized pectin characteristics. This study used the Response Surface Methodology (RSM) as the optimization method with the Central Composite Design (CCD) experimental design with Design Expert 13 software to determine the treatment combination based on time factors and solvent concentration. The treatment combination obtained was 11. The results showed that the maximum pectin yield value was 34.63% at a 7-minute extraction time using the citric acid solvent concentration of 20% and a validation value accuracy of 99.08%. The optimized pectin characteristics were a water content of 7.66%, ash content of 0.33%, equivalent weight of 183.28 mg, methoxyl content of 7.52%, galacturonic acid content of 67.13%, and degree of esterification of 63.56%. The pectin produced followed the pectin quality standards according to the International Pectin Producers Association (IPPA), except for the equivalent weight.Keywords: extraction, lemon albedo, pectin, ultrasonic AbstrakPektin merupakan bahan baku industri yang memiliki kemampuan dalam pembentukan gel, zat pengental, dan sebagai zat pengemulsi yang banyak diaplikasikan pada industri pangan dan non-pangan. Proses ekstraksi pektin dengan pelarut asam sitrat menggunakan bantuan gelombang ultrasonik dianggap lebih efektif dan efisien. Tujuan penelitian adalah untuk mendapatkan model optimasi proses produksi pektin hingga menghasilkan rendemen pektin yang maksimum dan mendapatkan karakteristik pektin hasil optimasi. Metode optimasi dalam penelitian ini menggunakan Response Surface Methodology (RSM) dengan dengan rancangan eksperimen Central Composite Design (CCD) menggunakan software Design Expert 13 untuk menentukan kombinasi perlakuan berdasarkan faktor waktu dan konsentrasi pelarut. Kombinasi perlakuan yang diperoleh adalah 11. Hasil penelitian menunjukkan bahwa nilai rendemen pektin maksimum adalah 34,63% pada waktu ekstraksi 7 menit dengan konsentrasi pelarut asam sitrat 20% dengan keakuratan nilai validasi adalah 99,08%. Karakteristik pektin hasil optimasi diperoleh nilai kadar air 7,66%, kadar abu 0,33%, berat ekuivalen 183,28 mg, kadar metoksil 7,52%, kadar asam galakturonat 67,13%, dan derajat esterifikasi 63,56%. Pektin yang dihasilkan sudah sesuai dengan standar mutu pektin menurut International Pectin Producers Association (IPPA) kecuali pada berat ekuivalen.Kata kunci: albedo lemon, ekstraksi, pektin, ultrasonik